If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(5a + 1) = -84 Reorder the terms: 6(1 + 5a) = -84 (1 * 6 + 5a * 6) = -84 (6 + 30a) = -84 Solving 6 + 30a = -84 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 30a = -84 + -6 Combine like terms: 6 + -6 = 0 0 + 30a = -84 + -6 30a = -84 + -6 Combine like terms: -84 + -6 = -90 30a = -90 Divide each side by '30'. a = -3 Simplifying a = -3
| 5-(-7a)=-33 | | 3x+38=8x-12 | | hj=328 | | 3r-8=-32x | | T=2lw+2lh+2wh | | 4n-4=6 | | -14x+18+2x=54 | | 2r-3.1=7 | | 192=-2x+8(5-7x) | | logx=1.22 | | n*-7-2=10 | | 3x-3(-5x+4)=-120 | | 2x+13=5y | | 11x-12-2x=15 | | 11mn-2mn+9= | | 0.23x=1.48 | | 259=7(8x+5) | | x^3+12x-24=0 | | 7r+6r=-13 | | 14x+1=-2+8x+15 | | -14=b-2-8 | | 7x+23-2x=53 | | 1+2x-3x=9 | | -143=9n-8 | | 46=2w+16 | | 8s-11s+6=9 | | 5y+13+15y=43 | | b^2+11b+28b=0 | | 7=-5+6m | | 5(2x-4)=11x+14+9x | | -11=-10+n*16 | | 8.25z=155.5 |